Utilization of Yeast as Feed Additive to Improve Ruminant Production - Elizabeth Wina (Indonesian Center for Animal Research and Development, 1999)
Yeast has been known and used in human life long time ago. Recently, yeast is used as feed additive for ruminant in overseas countries. There are a lot of strains and varieties of yeast but its type of strain or variety for ruminant feed is not mentioned. For ruminant feed, yeast is sold as live-cell yeast or mixture of yeast with its medium growth. Yeast can manipulate rumen by increasing cellulolytic bacteria so that the digestibility increased and consequently improving daily gain. The role of local yeast in improving ruminant production in Indonesia has not been deeply studied even though a good response found in the in vitro result. Key words: Yeast, Saccharomyces cerevisiae, ruminant, feed additive